EVALUATION OF THE EFFECTIVENESS OF THE ACTION OF CERTAIN PROTON PUMP INHIBITORS, CYTOPROTECTORS AND THEIR COMBINATIONS ON THE PERFORMANCE OF THE SYNTHESIS OF NITRIC OXIDE IN THE GASTRIC MUCOSA DURING INDOMETHACIN GASTROPATHY - Rakhmatullaeva, G.K.; Khamrayev, A.A.; Shukurova, F.; Parpibaeva, D.A. (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
To evaluate the effectiveness of the action of certain proton pump inhibitors, cytoprotectors, and their combinations on the performance of the synthesis of nitric oxide in the gastric mucosa in indomethacin gastropathy. Material and Methods: Biochemical studies were conducted on 14 groups of animals: 1 group - intact; Group 2 - animals with indomethacin gastropathy (IG); Group 3 - animals with IG treated with distilled water for 10 days (without treatment); Group 4 – animals with IG treated with omeprazole for 10 days; Group 5 - animals with IG treated with rabeprazole for 10 days; 6 group – animals with IG + de-nol – 10 days; Group 7 – animals with IG + sucralfat 10 days; Group 8 – animals with IG + pepsan-R – 10 days; Group 9 -– animals with IG + omeprazole + de-nol – 10 days; Group 10 – animals with IG + omeprazole + sucralfate – 10 days; Group 11 – animals with IG + omeprazole + pepsan-P – 10 days; 12 group – animals with IG + rabeprazol + de-nol – 10 days; Group 13 – animals with IG + rabeprazole + sucralfate - 10 days; 14 group - animals with IG + rabeprazole + pepsan-P – 10 days. For biochemical studies, animals were scored under ether anesthesia by single-step decapitation. Removed the stomach, washed, scraped mucous and slurried. Results: We found that de-nol and pepsan-P stimulate NO-formation, but sucralfate does not affect.Our results suggest that the effectiveness of de-nola and pepsan-P is due to their inductive effect on the activity of the key enzyme NO-formation - NADPH diaphorase. Conclusions: 1. Sucralfate does not affect these mechanisms. Rabeprazole, de-nol and pepsan-P to a single degree stimulate NO in the mucous tissue of the stomach during IG. 2. For the stimulation of NO-formation in the mucous tissue of the stomach is more effective is the combined use of rabeprazole with pepsan-P and rabeprazole with de-nol and less effective omeprazole with pepsan-R.